Multimodal Imaging of Torpedo Maculopathy With Fluorescence Adaptive Optics Imaging of Individual Retinal Pigmented Epithelial Cells - Vienola, Kari V.; Dansingani, Kunal K.; Eller, Andrew W.; Martel, Joseph N.; Snyder, Valerie C.; Rossi, Ethan A. (Frontiers in Medicine, 2021)
Torpedo maculopathy (TM) is a rare congenital defect of the retinal pigment epithelium (RPE). The RPE is often evaluated clinically using fundus autofluorescence (AF), a technique that visualizes RPE structure at the tissue level from the intrinsic AF of RPE fluorophores. TM lesions typically emit little or no AF, but this macroscopic assessment is unable to resolve the RPE cells, leaving the organization of the RPE cell mosaic in TM unknown. We used fluorescence adaptive optics scanning laser ophthalmoscopy (AOSLO) to show here for the first time the microscopic cellular-level structural alterations to the RPE cell mosaic in TM that underlie the tissue-level changes seen in conventional clinical imaging. We evaluated two patients with TM using conventional clinical imaging techniques and adaptive optics (AO) infrared autofluorescence (IRAF) in AOSLO. Confocal AOSLO revealed relatively normal cones outside the TM lesion but altered cone appearance within it and its margins in both patients. We quantified cone topography and RPE cell morphometry from the fovea to the margin of the lesion in case 1 and found cone density to be within the normal range across the locations imaged. However, RPE morphometric analysis revealed disrupted RPE cells outside the margin of the lesion; mean RPE cell area was greater than two standard deviations above the normative range up to ~1.5 mm from the lesion margin. Similar morphometric changes were seen to individual RPE cells in case 2. Multi-modal imaging with AOSLO reveals that RPE cells are abnormal in TM well beyond the margins of the characteristic TM lesion boundary defined with conventional clinical imaging. Since the TM fovea appears to be fully formed, with normal cone packing, it is possible that the congenital RPE defect in TM occurs relatively late in retinal development. This work demonstrates how cellular level imaging of the RPE can provide new insight into RPE pathologies, particularly for rare conditions such as TM.